Gastrointestinal manifestations of angioedema: a potential area of misdiagnosis. Issue 6 (23rd July 2020) - Mormile, Ilaria; Cocchiaro, Antonio; Bova, Maria; Loffredo, Stefania; de Paulis, Amato; Spadaro, Giuseppe; Petraroli, Angelica
Abstract : Abdominal pain is one of the most common conditions leading people to the emergency department. An uncommon but well described cause of abdominal pain is angioedema of the gastrointestinal tract due to recurrent angioedema without wheals. Abdominal involvement is very common in hereditary angioedema (HAE), but it is also described in acquired angioedema and allergic forms. In patients with HAE, the involvement of gastrointestinal tract with resultant abdominal pain occurs in 43–93% of cases. Attacks can involve the entire gastrointestinal tract, such as the oropharynx, small intestine, colon, liver, or pancreas. Pain is the most common gastrointestinal symptom, and it may occur for many years even without cutaneous or respiratory symptoms. The case report we included in this article emphasizes the importance of accurate evaluation of personal and family history in patients with a long history of acute, severe, and unexplained abdominal pain, and it gives an example of how diagnostic delay may be longer if gastroenterological symptoms are the predominant clinical presentation. Furthermore, sometimes the simultaneous presence of concomitant gastrointestinal disorders and HAE may cause difficulties in differential diagnosis. Gastroenterologists and other physicians should add HAE to their list of potential causes of unexplained abdominal pain. The initiation of appropriate prophylaxis and treatment will prevent needless suffering and useless surgical and medical procedures.